'Emergence of form': A recollection. (27th April 2012) - Münker, Katja
'The emergence of form' was an experimental framework that scrutinized 'the emergence of form' in the context of an intertwined exploration of different somatic practices and time-space-related reflections for an extended period of time: the duration of the complete conference. The framework was facilitated by the Aesthetic Practice and Embodiment Research Group of the Inter-University Centre for Dance Berlin – HZT represented by Professor Alex Arteaga, Elisabeth Molle, Katja Münker and Ka Rustler. Whilst the creation and realization of the project during the conference was a collective process, I have individually composed the text while being and moving on the floor. Passing through stages of the experiment and its embedment in the conference, I was listening and bringing into language with, in and from many layers of my living human system. Time-flow and time experience within the long-term experiment was particular not only because it was long, but because time-flow felt multi-layered and overlapping. The writing is trying to give that resonance. The intention behind this writing was to bridge and connect memory, experience, (sensuous and cognitive) reflection and evaluation without separating this subsequent act from the experiential-experimental setting of the framework itself.